Induction and suppression of tick cell antiviral RNAi responses by tick-borne flaviviruses. Issue 14 (22nd July 2014) - Schnettler, Esther; Tykalová, Hana; Watson, Mick; Sharma, Mayuri; Sterken, Mark G.; Obbard, Darren J.; Lewis, Samuel H.; McFarlane, Melanie; Bell-Sakyi, Lesley; Barry, Gerald; Weisheit, Sabine; Best, Sonja M.; et al.
Abstract: Arboviruses are transmitted by distantly related arthropod vectors such as mosquitoes (class Insecta ) and ticks (class Arachnida ). RNA interference (RNAi) is the major antiviral mechanism in arthropods against arboviruses. Unlike in mosquitoes, tick antiviral RNAi is not understood, although this information is important to compare arbovirus/host interactions in different classes of arbovirus vectos. Using an Ixodes scapularis- derived cell line, key Argonaute proteins involved in RNAi and the response against tick-borne Langat virus ( Flaviviridae ) replication were identified and phylogenetic relationships characterized. Analysis of small RNAs in infected cells showed the production of virus-derived small interfering RNAs (viRNAs), which are key molecules of the antiviral RNAi response. Importantly, viRNAs were longer (22 nucleotides) than those from other arbovirus vectors and mapped at highest frequency to the termini of the viral genome, as opposed to mosquito-borne flaviviruses. Moreover, tick-borne flaviviruses expressed subgenomic flavivirus RNAs that interfere with tick RNAi. Our results characterize the antiviral RNAi response in tick cells including phylogenetic analysis of genes encoding antiviral proteins, and viral interference with this pathway. This shows important differences in antiviral RNAi between the two major classes of arbovirus vectors, and our data broadens our understanding of arthropod antiviral RNAi.